Taxonomical and biological notes on Argentoleon irrigatus (Gerstaecker) (Neuroptera: Myrmeleontidae) - Girelli, Maria Eduarda; Tavares, Leon Gustavo Miranda; Machado, Renato Jose Pires (Zootaxa, 2024)
Argentoleon irrigatus (Gerstaecker), is a common antlion species, but with sparse figures and incomplete location records in the literature, whose genitalia and larvae remained undescribed. Herein, the adults are redescribed and immatures (larvae and pupa) are described for the first time, providing images of internal and external characters, including both male and female genitalia. The examination and illustration of these characters allowed us to better understand the position and the limits of the genus Argentoleon Stange, within the tribe Brachynemurini, including the differentiation of the larval stages of the closely related genus Austroleon Banks. Additionally, the distribution of Ar. irrigatus is updated and a map is elaborated, resulting in seven new state records for Brazil and a new country record from Colombia. Some biological aspects are also analyzed, regarding rearing in captivity and natural habitat, providing resources for future ecologic and biogeographical analyses. Furthermore, we analyzed the type specimens of the extensive synonymic list of Ar. irrigatus concluding that Austroleon stictogaster Navás, is in fact a synonym of Austroleon immitis (Walker), and not of Ar. irrigatus as currently accepted. Overall, a full taxonomic actualization of Ar. irrigatus is presented.